2015
DOI: 10.5152/npa.2015.7611
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Appraisals of Internal States and Duration of Remission in Remitted Bipolar Patients

Abstract: The results pointed out that dysfunctional cognitions may be utilized as possible indicators for the risk of relapse in clinical groups and vulnerability for BPD among other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In group studies comparing individuals with BD to other groups, individuals with BD consistently scored more highly on positive and negative appraisals of internal states compared to non-clinical controls ( Mansell, 2006 ; Alatiq et al, 2010 ; Mansell et al, 2011 ; Pavlickova et al, 2014 ; Ruggero et al, 2015 ; Tosun et al, 2015 ). Both extreme positive and negative appraisals (HAPPI) and positive self-referent appraisals of hypomanic states (HIQ) accurately predicted BD diagnosis ( Jones et al, 2006 ; Mansell and Jones, 2006 ; Mackali et al, 2014 ), controlling for current mood.…”
Section: Synthesis Of Findingsmentioning
confidence: 93%
See 3 more Smart Citations
“…In group studies comparing individuals with BD to other groups, individuals with BD consistently scored more highly on positive and negative appraisals of internal states compared to non-clinical controls ( Mansell, 2006 ; Alatiq et al, 2010 ; Mansell et al, 2011 ; Pavlickova et al, 2014 ; Ruggero et al, 2015 ; Tosun et al, 2015 ). Both extreme positive and negative appraisals (HAPPI) and positive self-referent appraisals of hypomanic states (HIQ) accurately predicted BD diagnosis ( Jones et al, 2006 ; Mansell and Jones, 2006 ; Mackali et al, 2014 ), controlling for current mood.…”
Section: Synthesis Of Findingsmentioning
confidence: 93%
“…Nine studies explored cross-sectional associations between extreme appraisals and mood symptoms, predominantly using student samples ( Jones and Day, 2008 ; Mansell et al, 2008 ; Dodd et al, 2010 , 2011a , 2013 ; Dempsey et al, 2011 ; Kelly et al, 2011 , 2016 ; Tosun et al, 2015 ; Dodd and Haigh, 2017 ; Haigh and Dodd, 2017 ). Extreme appraisals of internal states were consistently positively associated with activated mood ( Jones et al, 2006 ; Jones and Day, 2008 ; Dodd et al, 2011a , 2013 ; Kelly et al, 2011 ; Dodd and Haigh, 2017 ; Haigh and Dodd, 2017 ).…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found no differences in overall dysfunctional attitudes between healthy controls and in dividuals diagnosed with remitted BD (Alatiq et al, 2010;Lex et al, 2008;Lex et al, 2011;Mansell et al, 2011). Other studies found elevated DAS scores in patients with remitted BD relative to healthy control groups (Hollon et al, 1986;Jones et al, 2005;Scott et al, 2000;Tosun et al, 2015). However, dysfunctional attitudes refer to different areas, for example, achievement, dependency, and goal attainment.…”
mentioning
confidence: 99%